A secure group based authentication protocol for machine to machine communications in LTE-WLAN interworking architecture - Mariya Ouaissa; Abdallah Rhattoy (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Machine to Machine (M2M) communication has been used in applications such as telemetry, industry, automation and health. Support for a large number of devices has been considered an essential requirement in M2M communications. During this time, security is the most important challenge; M2M cannot access secure networks through effective authentication, all relevant M2M applications cannot be accepted. The challenge of M2M research is authentication by the group when a large number of M2M devices simultaneously accessing the network will cause severe authentication signaling congestion. The group based model under an M2M architecture, especially when the Machine Type Communication (MTC) devices belong to the non 3rd Generation Partnership Project (3GPP) network, will face a new challenge of access authentication. In this paper, we propose a group based authentication and key agreement protocol for machine type communications combining Elliptic Curve based Diffie-Hellman (ECDH) on the Extensible Authentication Protocol (EAP). Compared to EAP-AKA and other existing authentication protocols, our solution provides increased security against various malicious activities and better performance in terms of signaling overhead, bandwidth consumption and transmission cost.